2023
DOI: 10.1128/aem.00105-23
|View full text |Cite
|
Sign up to set email alerts
|

Serratia marcescens Colonization in a Neonatal Intensive Care Unit Has Multiple Sources, with Sink Drains as a Major Reservoir

Abstract: The bacterium Serratia marcescens is an important opportunistic human pathogen that thrives in many environments, can become multidrug resistant, and is often involved in nosocomial outbreaks in neonatal intensive care units (NICU). We evaluated the role of sinks during five suspected S. marcescens outbreaks in a NICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The bacterium is able to survive on various surfaces, including soap, and to rapidly spread among hospital patients, causing large nosocomial outbreaks, particularly in NICUs. 16 , 27 , 28 , 29 , 30 , 31 , 32 S. marcescens mainly colonize the environment (soil, plants, and animals) and recent genomic studies revealed that the nosocomial S. marcescens infections are mostly caused by a specific lineage of the bacterium (here called “Infectious clone”). 3 , 6 , 7 Considering the lethality of the bacterium, its fast-spreading capability and the existence of a strictly infection-associated lineage, a fast and precise detecting/typing method is required to establish effective infection control strategies in hospitals to prevent and to limit outbreaks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterium is able to survive on various surfaces, including soap, and to rapidly spread among hospital patients, causing large nosocomial outbreaks, particularly in NICUs. 16 , 27 , 28 , 29 , 30 , 31 , 32 S. marcescens mainly colonize the environment (soil, plants, and animals) and recent genomic studies revealed that the nosocomial S. marcescens infections are mostly caused by a specific lineage of the bacterium (here called “Infectious clone”). 3 , 6 , 7 Considering the lethality of the bacterium, its fast-spreading capability and the existence of a strictly infection-associated lineage, a fast and precise detecting/typing method is required to establish effective infection control strategies in hospitals to prevent and to limit outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…WGS remains the gold standard for the typing of the S. marcescens infection-associated lineage, and other high throughput sequencing methods such as HiSST proven to be successful in typing S. marcescens . 15 , 16 However, the time needed to carry out the sequencing may represent an important drawback. Indeed, this species is able to spread very rapidly among patients and can exploit different sources to grow in the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain differentiation primarily arises from the presence or absence of genes rather than nucleotide polymorphisms, indicating extensive genomic plasticity largely attributed to frequent horizontal gene transfers [ 25 , 60 , 61 ]. HiSST is a robust genotyping tool that provides highly reliable predictions for assessing clonality between strains [ 13 , 62 ]. However, in cases where two strains exhibit identical HiSST profiles, it is highly recommended to use WGS, especially for epidemiological investigations involving P. aeruginosa [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals represent a major site for the emergence and dissemination of multi-drug resistant (MDR) pathogens, such as carbapenemase-producing and extendedspectrum β-lactamase (ESBL)-producing Enterobacterales (CPE and ESBL-E, respectively), particularly in critical care units [5][6][7]. These MDR pathogens can colonise healthcareassociated (HCA) environmental reservoirs such as hospital sinks and contribute to healthcare-associated infections (HAIs), with many studies linking HAIs to sink drains [8][9][10],…”
Section: Introductionmentioning
confidence: 99%